2023
DOI: 10.1080/15476286.2023.2221511
|View full text |Cite
|
Sign up to set email alerts
|

The paralogues MAGOH and MAGOHB are oncogenic factors in high-grade gliomas and safeguard the splicing of cell division and cell cycle genes

Abstract: The exon junction complex (EJC) plays key roles throughout the lifespan of RNA and is particularly relevant in the nervous system. We investigated the roles of two EJC members, the paralogs MAGOH and MAGOHB, with respect to brain tumour development. High MAGOH/MAGOHB expression was observed in 14 tumour types; glioblastoma (GBM) showed the greatest difference compared to normal tissue. Increased MAGOH/MAGOHB expression was associated with poor prognosis in glioma patients, while knockdown of MAGOH/MAGOHB affec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…However, our understanding of the molecular mechanism of GC is still insufficient. MAGOH, a core protein involved in mRNA splicing, has been reported to be closely related to the occurrence and development of a variety of tumors [ 22 , 23 , 54 , 55 ]. For instance, Soederberg et al reported that the MAGOH and MAGOHB proteins were highly expressed in cutaneous melanoma cell lines and patient-derived tissue samples and that their knockdown significantly inhibited melanoma cell proliferation [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our understanding of the molecular mechanism of GC is still insufficient. MAGOH, a core protein involved in mRNA splicing, has been reported to be closely related to the occurrence and development of a variety of tumors [ 22 , 23 , 54 , 55 ]. For instance, Soederberg et al reported that the MAGOH and MAGOHB proteins were highly expressed in cutaneous melanoma cell lines and patient-derived tissue samples and that their knockdown significantly inhibited melanoma cell proliferation [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this effect was enhanced by the downregulation of both MAGOH and MAGOHB [ 22 ]. Barreiro et al revealed that the expression of MAGOH/MAGOHB was upregulated in brain tumors, especially in glioblastoma and that the decreased expression of MAGOH/MAGOHB led to changes in the splicing spectrum [ 23 ]. Similarly, our research group revealed that MAGOH was highly expressed in GC cells, that its knockdown inhibited the occurrence of GC by mediating b-RAF/MEK/ERK signaling and that the double knockdown of MAGOH and MAGOHB exerted better antitumor effects than did the single knockdown of MAGOH and MAGOHB, thus providing a potential new strategy for the treatment of GC [ 24 ].…”
Section: Introductionmentioning
confidence: 99%